Enhancing Permit Status Checking for the Integrated Public Service Information and Reporting System Application - Dwi Listriana Kusumastuti; Farhan Mubarak; Rehan Choirul Rohily; Sahtia Murti; Yulius Denny Prabowo; Emny Harna Yossy (LPPM Universitas Islam 45 Bekasi, 2023)
The district government of Sanggau already has a public service mall (MPP), which is used by all agencies as a place of service. SIPADU (Integrated Public Service Information and Reporting System) is the name of this application, which has various features to meet the needs of MPPs (Public Service Mall). Currently, users of the SIPADU application find it difficult to check the status of permissions. Users must first complete the authentication procedure in order to obtain the desired permission status. This research was conducted to implement a solution to make it easier for users to check the status of the submitted licensing by building a web-based system that will search for the data without requiring login authentication. The analytical methods used include Literature Study and Interview. The design method used is the waterfall method with 6 stages of the process, namely Planning, Analysis, Design, Implementation, Testing, and Verification. The result of this system is a website that can check the status of the permit being submitted. The results of the User Interface evaluation are following the provisions of the Eight Golden Rules method and the results of the evaluation of system testing using the BlackBox testing method with the results showing 100% no errors occur so that it is very suitable for use by users. This study applies the Web Scraping method using PHP scripts and using the Apache Web Server to obtain all licensing data using authentication data provided by PT Media Visual Group so that all users of the SIPADU application can track licensing.